Identity and Islamic Radicalization in Western Europe - Syed Mansoob Murshed; Sara Pavan (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper argues that both socio-economic disadvantage and political factors, such as the West's foreign policy with regard to the Muslim world, along with historical grievances, play a part in the development of Islamic radicalized collective action in Western Europe. We emphasise the role of group identity based individual behaviour in organising collective action within radicalized Muslim groups. Inasmuch as culture plays any role at all in radicalization, it is because individuals feel an imperative to act on the basis of their Muslim identity, something to which different individuals will attach varying degrees of salience, depending on how they place their Muslim identity based actions in the scheme of their multiple identities. We also emphasize the role of the opportunistic politician, from the majority European community, in fomenting hatred for Muslims, which also produces a backlash from radicalized political Islam. We present comparative evidence on socio-economic, political and cultural disadvantage faced by Muslim minorities in five West European countries: Germany, the UK, France, Spain and the Netherlands.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; Identity; Radicalization; Clash of civilizations; Terrorism